ANALISIS ILUSTRASI SATIR SEBAGAI MEDIA EDUKASI DAN KESADARAN SOSIAL : STUDI KASUS KARYA @WIRTAMS - Satira Az Zahrah, Azwa (SNADES, 2025)
Satirical illustration is a form of visual communication that not only conveys messages but also deconstructs dominant discourses and invites the public to critically reflect on social realities. In the context of social education, illustration holds significant potential as an educational medium that engages diverse audiences both emotionally and intellectually. This study examines the works posted on Instagram account @wirtams, which critiques the Free Nutritious Meal (MBG) program through an ironic and reflective visual approach. The illustration sparked public debate on social media, revealing a range of audience responses. Findings indicate that satirical illustration can activate social participation and open space for public advocacy. Its strength lies in its ability to construct tension between idealized imagery and the lived experiences of marginalized groups. To uncover the embedded meanings, this research employs a descriptive qualitative method with Roland Barthes’ semiotic approach, analyzing layers of denotation, connotation, and myth within the visual construction. The analysis affirms that visual communication design can serve as an effective tool for advocacy when developed contextually, critically, and responsively toward social issues.